Penggunaan Model Pembelajaran Somatic Auditory Visualisation Intellectualy Untuk Meningkatkan Hasil Dan Motivasi Belajar Siswa Kelas X SMA Negeri 1 Sinunukan Pada Materi Fungsi Logaritma - Torang Siregar; Lelya Hilda; Almira Amir; Suparni (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
The ability to absorb the national assessment of logarithmic function content for SMA Negeri 1 Sinunukan in 2020 and 2021 is very low. This low learning ability may be caused by the implementation of less effective learning strategies. Therefore, there is a need to use more effective learning strategies so that students master mathematics. especially the material on logarithmic functions becomes better and students' learning motivation also changes for the better. One learning strategy that is considered to have the potential to improve academic achievement and increase motivation to learn mathematics is the SAVI learning model. The aim of this research is to find out whether the learning model SAVI can increase the motivation and learning outcomes of logarithm material for class Both cycles use the SAVI learning model. 0.97 in cycle I increased in cycle II to 77.56